Something is wrong in the complex model of the lithosphere of the continental margins of the Antarctic Peninsula - Rusakov, O. M. (Geofizicheskiy Zhurnal, 2011)
The analysis has been made of j oint geophysical and p etrological models for the lithosphere structure of the Antarctic Peninsula continental margin.